Síndrome de Takotsubo: complicación cardiovascular del accidente cerebrovascular - Leiva Abanto, Claudio (2022)
An 82-year-old woman, Katz A, with a history of type 2 diabetes mellitus and high blood pressure, was admitted for ischemic stroke complicated by Takotsubo ́s syndrome with subsequent readmission for atrial fibrillation after discharge. These three clinical events have criteria to be integrated as a Brain Heart Syndrome, which is a high-risk condition for mortality.